Autumn Application of Synthetic Auxin Herbicide for Weed Control in Cereals in Poland and Germany - Łukasz Sobiech; Andrzej Joniec; Barbara Loryś; Janusz Rogulski; Monika Grzanka; Robert Idziak (Agriculture, 2022)
The biological efficacy of herbicides MCPA+tribenuron-methyl (code name: MT-565 SG) and diflufenican+chlorotoluron (Legato Pro 425 SC) was estimated in eighteen field experiments on winter cereals in Poland and Germany to control broadleaf weeds. Postemergence application of tribenuron-methyl in combination with MCPA, applied at the 3-leaf stage to 3 tillers detectable in autumn in winter cereals, resulted in the majority of weed species occurring in autumn being effectively eliminated with MCPA+tribenuron-methyl applied at 1.0 kg∙ha–1. It also provided an acceptable (82.4–94.1%) and comparable level of control to commonly occurring weeds Brassica napus, Capsella bursa-pastoris, Centaurea cyanus, Lamium purpureum, Tripleurospermum inodorum, Stellaria media, and Thlaspi arvense. A satisfactory level of control of 66.3 to 88.3% was confirmed for Veronica persica, Viola arvensis, and Galium aparine. According to these results, the formulation of tribenuron-methyl combined with MCPA can be recommended for application in winter cereals in the autumn as an alternative to commonly available herbicides.